2016
DOI: 10.1039/c5ra24638e
|View full text |Cite
|
Sign up to set email alerts
|

A novel high temperature retarder applied to a long cementing interval

Abstract: A retarder comprised of sodium styrene sulfonate, itaconic acid and hydroxyethyl methacrylate was synthesized by aqueous free radical copolymerization, which can be applied to a long cementing interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 4 publications
(3 reference statements)
0
13
0
Order By: Relevance
“…The various molecular weight of FDA‐II and its distribution are listed in Table . It can be concluded that the synthesized polymer possesses a relatively high molecular weight ( M n = 298,426 g mol −1 , M w = 645,580 g mol −1 ) and a broad polydispersity index (PDI) of 2.1934, typical for radical polymerization . The high molecular weight is an important characteristic of the synthetic polymer used as fluid loss additive for cementing, which can keep the liquid phase viscosity effectively and prevent the filtrate from invading into the formation or reservoir stratum through aggrandizing its fluid resistance.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…The various molecular weight of FDA‐II and its distribution are listed in Table . It can be concluded that the synthesized polymer possesses a relatively high molecular weight ( M n = 298,426 g mol −1 , M w = 645,580 g mol −1 ) and a broad polydispersity index (PDI) of 2.1934, typical for radical polymerization . The high molecular weight is an important characteristic of the synthetic polymer used as fluid loss additive for cementing, which can keep the liquid phase viscosity effectively and prevent the filtrate from invading into the formation or reservoir stratum through aggrandizing its fluid resistance.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…5 But with the continuous increase of complex well conditions such as deep wells and ultra-deep wells, and higher requirements have been put forward for oil well cement retarders. 6 Commonly, the retarders as an indispensable functional additive for deep well and ultra-deep well cement slurry, which have wide variety, mainly including lignosulfonate, hydroxycarboxylic acid and its salts, polyols and their derivatives, inorganic salts, and carbohydrate compounds. [7][8][9][10][11] Overall, the retarders can be divided into organic compounds and polymers depends on the synthesis methods, molecular structure, and weight.…”
Section: Introductionmentioning
confidence: 99%
“…Though the thickening time or setting time is effectively prolonged, the thickening curve of cement slurry containing retarders shows a obvious bulging phenomenon attributed to the decomposition of function groups and molecule chains under high temperature conditions. 12 …”
Section: Introductionmentioning
confidence: 99%
“…This negatively charged layer not only inhibits the hydration process of cement attributed to the shielding effect of polymer layer, but also is favorable to the dispersion of cement particles because of electrostatic repulsion between the cement particles. [18][19][20] The heterogeneous charge distribution on the surface of hydrating cement particles should be responsible for the adsorption behaviors between the cement particles and the retarders.…”
mentioning
confidence: 99%